FUNDAMENTAL RISK, SYSTEMATIC RISK AND SHARE PRICE OF THE COMPANY CONSUMPTION GOODS INDUSTRIAL SECTOR - Annissa Yunita Uli; Lana Sularto (Universitas Gunadarma, 2009)
Financial analysis is a must for an investor before deciding to invest. Generally, on share investment financial analysis is done using fundamental analysis and/or technical analysis. As addition to fundamental analysis, an investor also should be aware of market risk or systematic risk in generally speaking. Market risk is correlated heavily with certain kind of share price or certain group due to investor anticipation toward rate or return expected.However, this risk can be measured using beta (β). This research is intended to evaluate the effect of fundamental analysis and systematic risk on share price, whether it is partially or simultaneous. Sampling was done using purposive sampling, i.e. by choosing 31 companies which are listed in Stock Exchange Indonesia and publish financial report during year 2006-2008. Data analysis was done using multiple regressions from statistics method, by deploying SPSS software. Dependent variables is share price, and independents variables are return on asset, return on equity, dividend payout ratio, debt to equity ratio, book value, required rate of return, and beta (β). Result shows that only book value influence share price partially. Simultaneously, variables are return on asset, return on equity, dividend payout ratio, debt to equity ratio, book value, required rate of return, and beta (β) influence share price.Key words: fundamental factor, systematic risk, and share price.